Isolated Orbital Floor Fracture Management: A Survey and Comparison of American Oculofacial and Facial Plastic Surgeon Preferences - Cohen, Liza M. (Craniomaxillofac Trauma Reconstr, 2019)
This article aimed to characterize, compare, and contrast the management of isolated orbital floor fractures among oculofacial and facial plastic surgeons in the United States. An anonymous 17-question multiple-choice web-based survey was distributed to all 590 members of the American Society of Ophthalmic Plastic and Reconstructive Surgery (ASOPRS) and all 1,300 members of the American Academy of Facial Plastic and Reconstructive Surgery (AAFPRS) using each society's email database from November 2016 to January 2017. Two-hundred twenty-five oculofacial and 135 facial plastic surgeons completed the survey. The most important indications for surgery among both oculofacial and facial plastic surgeons were motility restriction, enophthalmos, and diplopia at 2 weeks. The most common preferred time to surgical intervention was 8 to 14 days; however, facial plastic surgeons were more likely to operate after 4 to 7 days ( p  < 0.001). The most common choices of orbital implant material were porous polyethylene and porous polyethylene plus titanium for both oculofacial and facial plastic surgeons, nylon for oculofacial surgeons, and titanium for facial plastic surgeons. The majority rarely/never used intraoperative computed tomography imaging or navigation. Facial plastic surgeons were more likely to perform postoperative imaging ( p  < 0.001). We report results of the first survey of isolated orbital floor fracture management among oculofacial and facial plastic surgeons in the United States. This survey characterizes practice patterns and areas of similarities/differences among oculofacial and facial plastic surgeons in the management of isolated orbital floor fractures, which may help define the current standard of care.